Potency of Food Cluster to Improve the Quality of Creative Industries - ., Widiyanto; Kurnia Pitaloka, Lola (KnE Social Sciences, 2020)
Creative economy is an economic concept that promotes the creativity of the players with the idea of relying on human resources as a factor of production by creating creativity as a resource that can always be updated in the process of economic activity and is expected to drive sustainable economic growth. Creative economic players culinary subsector is hardly detected due where are the players, although provided center point for culinary players but limited place for players an obstacle. Reconvene the concentration of culinary subsector or providing more places to be the center point for the perpetrators culinary subsector so that all have the same opportunity to widely known. Location of this research is in the Semarang City. Methods of data collection used interviews and documentation. Analysis data methods used spider web to see the area of convergence and determine convergence area in accordance with the state of the region and the state of the environment. Descriptive analysis is used to describe a general overview and potential concentration. Population in this study is all creative economic players of culinary subsector. Related parties are used as a resource is the Department of Cooperatives and SMEs, the Department of Tourism, Department of Industry and the Association of creative economic players culinary subsector and elements of the creative economy businesses modern. Sample in this study used stratifie random sampling. Informants selected for samples are (1) the related department for culinary subsector; (2) creative economic players culinary subsector; (3) academics and associations that give high attention on the creative economy culinary subsector. The results of this study are (1) a development area of economic creative subsector culinary divided into five distinct regions, there are six center point subsector culinary established by the Government of Semarang, the area Simpang Lima, Chinatown, SMEs Center Banyumanik, Pekunden district, Pandanaran district and SMEs Gallery in the Old City; (2) Based on the distribution of types of cuisine can be divided into four areas based on its type, namely (a) the type of center souvenirs will be concentrated in Banyumanik and Central Semarang (b) the type of café is located in Central Semarang, South Semarang and Tembalang; (c) the type of meals centered in the region of Central and South Semarang and (d) the type of streetfood concentrated in one region, namely South Semarang. the conclusions of this studys are (a) necessary for the government to increase the number of concentration for a culinary subsector because there are many players who have failed the creative economy; (B) the need for training for a culinary subsector creative economic players to want to join and use the concentration of efforts in order to facilitate the arrangement of the environment and to maintain the comfort and cleanliness of the environment; (C) the need for policing, especially health and hygiene environment for creative economic players after selling. Keywords: Creative Economy, Culinary Subsector, Center Point, Development, SMEs